O contexto da gestão dos resíduos sólidos urbanos no município de Uberlândia-MG e a tendência dos novos conceitos e princípios que orientam a economia circular - Abdalla, Fernando Antônio (2018)
Increased consumption of durable and non-durable goods has expanded across most of the planet. Except for regions with predominantly high poverty rates, consumerism has become a "necessity" in the modern way of life. This phenomenon, which began with the industrial revolution, has been causing irreversible side effects, cases of harmful environmental impacts on the atmosphere, oceans, seas, rivers, lakes and soils. As a consequence, human health and quality of life conditions are constantly being threatened, mainly by contaminant residues - and potential residues - from the production and consumption of industrialized products on a large scale. Waste reflects the most obscure face of this scenario. It transmits a pseudo-sensation of infinity of natural resources. Even in countries with high levels of economic development such negative impacts are perceptible, which leads us to believe that a significant change in social consumption behavior is necessary. Meanwhile, the final adequate disposal of urban solid waste should not be perceived as an isolated alternative, but rather a fundamental step of the process, preceded, obviously, by selective collection. Assuming this process is an indispensable responsibility of sectoral public policies. Antagonistically, in this chaotic scenario, there is growing adherence to the new concepts and principles of the Circular economy, which have been building innovative and "revolutionary" proposals. The so-called Circular Economy, this, arises in opposition to the already established and usual concepts and practices of the Linear Economy. Therefore, this work aims to present these two antagonistic ideological currents and the practices that permeate each one's actions and challenges, seeking to contextualize through the example of the experience lived in the municipality of Uberlândia-MG, whose actions and programs are guided by the pragmatism of the Linear Economy , in order to establish causal nexus, describing the new global trend, anchored under the paradigm called Circular Economy.